Réponses

  • Utilisateur Brainly
2014-09-07T10:36:28+02:00
Ex 6 :

S= 7 - 13 + 2 - (- 14 + 6 - 3)
S= 7 - 13 + 2 - (- 11)
S= - 4 + 11
S= 7

T= [- 10,6 - (0,6 + 1,2)] - (5,7 - 9,8)
T= (- 10,6 - 1,8) - (- 4,1)
T= - 12,4 + 4,1
T= - 8,3

U= - [5,5 - (4,6 - 17,1)] - (- 12,6 + 4,9)
U= - (5,5 + 12,5) + 7,7
U= - 18 + 7,7
U= - 10,3
2014-09-07T10:42:05+02:00
Exercice  6  :

S = 7 - 13 + 2 - (- 14 + 6 - 3)
S = 7 - 13 + 2 - (- 11)
S = - 4 + 11
S = 7

T = (- 10,6 - (0,6 + 1,2)) - (5,7 - 9,8)
T = (- 10,6 - 1,8) - (- 4,1)
T = - 12,4 + 4,1
T = - 8,3

U = - (5,5 - (4,6 - 17,1)) - (- 12,6 + 4,9)
U = - 5,5 - (- 12,5) - (- 7,7)
U = - 5,5 + 12,5 + 7,7
U = - 5,5 + 20,4
U = 14,9